Screening for second primary tumors in the aerodigestive tract in non-Asian populations with head and neck cancer – systematic review and meta-analysis - A.D.I. Maan; S.E.M. van de Ven; S. Keereweer; R. Cornelissen; P.D. Siersema; A.D. Koch (ESMO Gastrointestinal Oncology)
Background: Patients diagnosed with a primary tumor in the esophagus, lungs, or head and neck are at an increased risk for developing second primary tumors (SPTs) in these regions. Most studies on SPT prevalence focus on Asian populations, with limited data available for non-Asian groups, leaving the utility of screening unclear. This review aims to assess the yield of screening for SPTs in non-Asian populations following a primary tumor in these regions. Patients and methods: A systematic literature search was conducted to identify studies on screening for esophageal, lung, or head and neck SPTs after a primary tumor diagnosis in any of these sites. The primary outcome was the prevalence by screening of all diagnosed SPTs in the esophagus, head and neck or lungs. Results: Due to limited data on screening for SPTs after esophageal or lung tumors, this review focused solely on screening after primary head and neck tumors. A total of 26 studies with 8071 patients from non-Asian countries were included. The pooled prevalence for all SPTs was 5.4% [95% confidence interval (CI) 4.1% to 7.2%]. The pooled prevalence for esophageal SPTs individually was 5.3% (95% CI 3.7% to 7.7%), for head and neck SPTs 4.6% (95% CI 1.0% to 18.1%) and for lung SPTs 4.0% (95% CI 2.6% to 6.2%). Most SPTs were detected in combination with an index hypopharynx carcinoma (60.0%). The proportion of synchronous (45.3%) and metachronous (54.7%) SPTs was similar. Conclusion: Endoscopic screening for esophageal SPTs in non-Asian countries should be considered, especially in patients with a primary hypopharynx carcinoma.